Studi Literatur Aktivitas Antelmintik Ekstrak Etanol Biji Pinang (Areca catechu L.) dan Palem Putri (Veitchia merillii L.) - Atiqoturrohmaniyyah; Ratu Choesrina (Bandung Conference Series: Pharmacy, 2022)
Abstract. Worm infection is an infectious disease caused by worm parasites and has infected more than 2 billion people worldwide, especially in developing countries such as Indonesia. Based on the experience of the community for generations, pinang (Areca catechu Linn) and palem putri (Veitchia merrillii) have potential as anthelmintics. The purpose of this literature study was to determine the anthelmintic activity of ethanol extract seeds pinang (Areca catechu L.) and palem putri (Veitchia merrillii L.) against adult worms and to determine the class of secondary metabolites from ethanol extract seeds pinang (Areca catechu L.) and palem putri (Veitchia merrillii L.) which have anthelmintic potential. This research was conducted using a systematic literature review method which was derived from 4 national articles and 1 international article. The results showed that the ethanol extract seeds pinang (Areca catechu L.) and palem putri (Veitchia merrillii) had anthelmintic activity against Ascaris lumbricoides, Ascaris suum and Ascaridia galli worms which experienced paralysis and also death. The ethanol extract of seeds pinang (Areca catechu L.) and palem putri (Veitchia merrillii) contains a class of secondary metabolites are alkaloids, flavonoids, saponins and tannins. The conclusion from this literature study is that the ethanol extracts seeds pinang (Areca catechu L.) and palem putri (Veitchia merrillii) have potential as anthelmintics and the results of phytochemical screening of the ethanol extracts seeds pinang (Areca catechu L.) and palem putri (Veitchia merillii L.) showed the presence of content of secondary metabolites are alkaloids, flavonoids, tannins and saponins which are thought to have anthelmintic activity. Abstrak. Infeksi cacing merupakan penyakit infeksi yang disebabkan oleh parasit cacing dan sudah menjangkit lebih dari 2 milyar manusia di seluruh dunia terutama di negara berkembang seperti Indonesia. Berdasarkan pengalaman masyarakat secara turun temurun tanaman pinang (Areca catechu Linn) dan palem putri (Veitchia merrillii) berpotensi sebagai antelmintik. Tujuan dari dilakukannya studi literatur ini adalah untuk mengetahui aktivitas antelmintik ekstrak etanol biji pinang (Areca catechu Linn) dan palem putri (Veitchia merrillii) terhadap cacing dewasa serta mengetahui golongan metabolit sekunder dari ekstrak etanol biji pinang (Areca catechu Linn) dan palem putri (Veitchia merrillii) yang berpotensi sebagai antelmintik. Penelitian ini dilakukan dengan metode systematic literature review yang berasal dari 4 artikel nasional dan 1 artikel internasional. Hasil yang didapatkan menunjukkan bahwa ekstrak etanol biji pinang (Areca catechu Linn) dan palem putri (Veitchia merrillii) memiliki aktivitas antelmintik terhadap cacing Ascaris lumbricoides, Ascaris suum dan Ascaridia galli yang mengalami paralisis dan juga kematian. Ekstrak etanol biji pinang (Areca catechu Linn) dan palem putri (Veitchia merrillii) mengandung golongan senyawa metabolit sekunder yaitu alkaloid, flavonoid, saponin dan tanin. Kesimpulan dari studi literatur ini yaitu ekstrak etanol biji pinang (Areca catechu Linn) dan palem putri (Veitchia merrillii) berpotensi sebagai antelmintik dan hasil skrining fitokimia ekstrak etanol biji pinang (Areca catechu L.) dan palem putri (Veitchia merillii L.) menunjukkan adanya kandungan senyawa metabolit sekunder yaitu alkaloid, flavonoid, tanin dan saponin yang diduga memiliki aktivitas sebagai antelmintik.